Haplotype Variations and Genetic Structure of Indonesian Green Leafhopper Nephotettix virescens (Distant.) (Hemiptera: Cicadellidae) Population based on Cytochrome C Oxidase I and II Genes - Rafika Yuniawati,; Rika Raffiudin,; Made Samudra, (Tropical Life Sciences Research, 2019)
The green leafhopper (GLH), Nephotettix virescens (Hemiptera: Cicadellidae) is an insect vector of the important rice tungro viruses. Currently, information on cytochrome c oxidase (COI and COII) genetic variation in N. virescens in Indonesia is unknown. This study investigated the haplotype variations of N. virescens populations that were collected from eight locations in six Indonesian provinces, i.e. Aceh, West Java, Central Java, East Java, Bali and South Sulawesi. Primers for the COI and COII genes of N. virescens were then designed based on N. cincticeps (GenBank KP749836). Two groups of sequences of the mitochondrial DNA gene, i.e. COI (735 base pairs) and COII (612 bp), were used to investigate the green leafhopper haplotype variations. There were 128 sequences of COI and COII obtained from eight populations. Of the 64 GLH individuals, there were 14 COI haplotypes with one common and 13 specific haplotypes, and 10 COII haplotypes with two common and eight specific haplotypes. Based on COI gene, we found four group of haplotypes from Sumatera, Jawa, Bali and Sulawesi. These haplotype variations are applicable as a DNA marker for Indonesian N. virescens identification. Our results have important implications for monitoring and control of this important agriculture insect.